EFFECT OF FECL3 AND AL2O3 ADDITION TOWARD LIGNIN CONTENT ON CORN COB DELIGNIFICATION WITH NAOH AS THE SOLVENT BY USING ULTRA SONIC ASSISTED - Kanani, Nufus; Rusdi, Rusdi (World Chemical Engineering Journal, 2019)
Corn cobs are one of the many lignocellulosic wastes highly available all over Indonesia, one of them is in Banten. Lignocellulosic waste is agricultural waste containing cellulose, hemicellulose, and lignin. Corn cobs contain cellulose (40-60%), hemicellulose (20-30%) and lignin (15-30%). To be able to utilize the cellulose content contained in corn cobs optimally, it is necessary to separate the lignin content in corn cobs. This study aims to examine the effect of the addition of FeCl3 and AL2O3 on the delignification process of corn cob with NaOH solvent using ultrasonic waves. In the previous study, 40% lignin in cellulose was obtained by using NaOH solvents with the help of ultrasonic waves at a temperature of 60 0C and an ultrasonic frequency of 40 KHz. Therefore, in this study a delignification process was carried out at a temperature of 60 0C with an ultrasonic frequency of 40 kHz with the addition of FeCl3: NaOH, AL2O3: NaOH, AL2O3: FeCl3 and FeCl3: AL2O3 0: 1; 1: 1 and 2: 1 respectively. The test results using the Chesson method showed that the lowest lignin content in cellulose was 12% at the ratio of NaOH: AL2O3 as1: 2.